Modern Retail Regulations in Sidoarjo Regency after the issuance of Sidoarjo Regional Regulation Number 10 of 2019 concerning Supermarket Arrangement in Sidoarjo Regency - Pratama, Candra Surya; Mediawati, Noor Fatimah; Purwaningsih, Sri Budi; Phahlevy, Rifqi Ridlo (Indonesian Journal of Public Policy Review, 2020)
Modern retail is a business channel selling consumer goods directly and indirectly with the fastest growth for consumer goods companies in Indonesia. With the rapid growth of the modern retail business in the Sidoarjo area, it is enough to cover the existence of traditional retail in the vicinity. After the enactment of the Sidoarjo Regency Regulation Number 10 of 2019 concerning Supermarket Arrangement in Sidoarjo Regency, can the regulation provide protection and maintain the consistency of the existence of traditional retail amidst the proliferation of modern retail. The research uses normative research based on the legal approach. With the changes in the Regional Regulation of Sidoarjo Regency Number 10 of 2019 concerning Arrangement of Supermarkets in Sidoarjo Regency from the previous regulation, Regent's Regulation Number 36 of 2016 concerning Arrangement of existing Minimarkets and the changes made.